Combination Therapy for Psoriasis with Methotrexate and Other Oral Disease-Modifying Antirheumatic Drugs: A Systematic Review - Tyng-Shiuan Hsieh; Tsen-Fang Tsai (Adis, Springer Healthcare, 2023)
Abstract Introduction Although the introduction of biologics and targeted synthetic disease-modifying antirheumatic drugs (tsDMARDs) has reshaped the treatment paradigm for immune-mediated inflammatory diseases (IMIDs) such as psoriasis, oral conventional synthetic DMARDs (csDMARDs) remain the cornerstone in their treatment. Combinational use of DMARDs is common in rheumatological practice, but for the treatment of many skin diseases, dermatologists typically use a single oral DMARD, with methotrexate (MTX) being the most commonly prescribed csDMARD for psoriasis. Methods To better understand the potential benefits of MTX combination therapy in psoriasis, a literature review was conducted using Medline (PubMed), Embase, Web of Science, and the Cochrane Library, covering articles published from inception until October 2022. Randomized controlled trials, cohort, open-label, and observational studies, and case reports with efficacy and safety results for combination therapy with MTX, csDMARDs, and tsDMARDs or comparisons between MTX monotherapy and combination therapy with other oral DMARDs in psoriasis were included. Studies involving MTX monotherapy alone or sequential treatment with MTX and other oral DMARDs were excluded, as were non-English articles. The results are presented as a systematic review, and the risk of bias was assessed by the corresponding author using the Cochrane Handbook for Systematic Reviews of Interventions, version 6.3, and confirmed by an independent assessor. Results Eleven studies comprising 494 participants were included in the review. Overall, combination treatment with MTX and other oral DMARDs exhibited good efficacy and tolerability in psoriasis. However, the included studies were primarily small scale or retrospective, and larger prospective randomized trials are needed to provide stronger evidence. Conclusion This literature review suggests that combination therapy with MTX and csDMARDs may serve as an efficacious treatment for psoriasis patients with an inadequate response to oral DMARD monotherapy.